Molecular Confirmation of the Relationship between Candida guilliermondii Fks1p Naturally Occurring Amino Acid Substitutions and Its Intrinsic Reduced Echinocandin Susceptibility - Dudiuk, Catiana Beatriz (2017)
C. guilliermondii shows intrinsic reduced echinocandin susceptibility. It harbors two polymorphisms (L633M and T634A) at the Fks1p hot-spot 1 region. Our objective was to confirm that C. guilliermondii´s reduced echinocandin susceptibility is due to those naturally occurring substitutions. We constructed a Saccharomyces cerevisiae mutant where a region of its FKS1 gene (including hot-spot 1) was replaced with that from C. guilliermondii The chimeric mutants showed 32-fold echinocandin MIC values increase confirming the hypothesis.